Usaha Gula Aren Ditinjau dari Pendapatan dan Faktor-faktor yang Memengaruhi Pengrajin Melakukan Usaha Gula Aren di Desa Ciranggem Kecamatan Jatigede Kabupaten Sumedang - Rochdiani, Dini; Charina, Anne; Deliana, Yosini; Trimo, Lucyana; Pardian, Pandi; Supyandi, Dika (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Palm sugar is a processed product from palm trees (nira) which is cultivated by many craftsmen, especially UMKM craftsmen. Activity of UMKM is an effort to increase income for palm sugar craftsmen. However, there are still obstacles in its development, namely the difficulty of obtaining raw materials in the form of nira because it is related to tradition and the low selling price of palm sugar. This low price results in the craftsmen's income being low. Generally, craftsmen never take into account production costs in detail, so that the income they earn cannot be calculated with certainty. The aim of this research is to calculate the costs and income of palm sugar craftsmen, as well as the factors that influence craftsmen to run a palm sugar business. The research method used is a case study in Ciranggem Village, Jatigede District, Sumedang Regency by taking 10 palm sugar craftsmen with census. The research results show that for one palm sugar production process, the average cost incurred is Rp. 164,000 and produces 10 kg of palm sugar. The selling price for palm sugar is Rp. 20,000/kg, so the income earned is Rp. 36,000/one production process. The R/C for palm sugar is 1.22, meaning that the palm sugar business is worth pursuing. The factors that most influence craftsmen to cultivate palm sugar are to increase family income.